Linking Surface Water Content to Groundwater Levels in Tropical Peatlands: Insights from the van Genuchten Approach - Putri, Atfi Indriany; Danoedoro, Projo; Sulaiman, Albertus; Sekaranom, Andung Bayu (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Tropical peatland in Indonesia have always been characterized by Peat Hydrology Units which have a function as a large amount of carbon storage and are able to regulate the hydrological cycle naturally. This study has two objectives, namely to analyze the variability of SWC, GWL, and rainfall parameters, to be able to understand the patterns of hydrological interactions in peatlandecosystems and to explain the quantitative relationship between SWC and GWL parameters using the van Genuchten Equation (VG) approach. The study also uses a VG based soil hydraulic curve modeling approach to describe groundwater retention and its impact on groundwater surface dynamics. The results showed that the SWC value was significantly influenced by the depth of theGWL and the intensity of rainfall, this underlined that the relationship between the two parameters is reciprocal. In addition, understanding the relationship between these parameters is very important, since the SWC value greatly determines the moisture status of the peat surface, in addition to directly the SWC value also affects the susceptibility of peat fires, while the GWLregulates the long-term hydrological balance and carbon emission potential. Therefore, conducting this study can improve understanding of hydrological feedback in peatlands. The results of the correlation analysis between parameters in this study showed that there was a strong relationship between SWC and GWL (R² = 0.6–0.8), while the correlation between GWL and Rainfall was weak(R² = 0.1–0.2). This suggests that SWC variation is primarily influenced by groundwater fluctuations rather than precipitation.